The decarbonization of gas in the Southern Cone of South America - Ieda Gomes; Luciano Caratori; Hernan Carlino; Fernanda Delgado; Luara Sousa (The Oxford Institute for Energy Studies, 2021)
South America is endowed with vast energy resources and natural gas plays an important role in the supply of energy to the region. A few countries in the Southern Cone area such as Argentina, Brazil and Chile, also meet part of their demand needs with imported liquefied natural gas (LNG) and/or pipeline gas. In line with the objectives of diversifying to indigenous sources, reduce GHG emissions and advance the Paris Agenda towards net-zero emissions, there has been a push to increase the use of renewable sources in those countries, mainly solar and wind. In 2019 the installed capacity of wind energy more than doubled in Argentina year-on-year (albeit from a small base) whilst solar grew 19.6 per cent and 23.9 per cent in Brazil and Chile respectively. For many years, South American countries have been looking for viable ways to develop decarbonized gas such as biomethane, biogas and, more recently, hydrogen. This paper analyzes the efforts by Argentina, Brazil and Chile to decarbonize gas to reduce greenhouse gases emissions, including some significant projects already being developed and in operation. The paper also assesses the initiatives, timing and challenges, and describe the bottlenecks - including costs, infrastructure, financing and regulatory issues - impacting on the development of projects and the more widespread use of biogas, biomethane and hydrogen in these economies. Finally, the possibility of creating a regional market for decarbonized gas is investigated. Looking at the region overall, there is significant potential for biogas and biomethane in Argentina and Brazil, but less so in Chile. In order to realise that potential, particularly for biomethane further incentives and regulations will be required. For hydrogen, while PV seems to be the most competitive source for green hydrogen, levelised costs of green hydrogen remain at least double the cost of hydrogen from natural gas without CCUS. Although the three countries are pursuing decarbonised gas projects, initial planning is still in progress and there is a lack of sufficient coordination between government and policy makers to drive the development. Particularly for hydrogen, large scale developments are likely to be beyond the current NDC horizon of 2030, but putting a clear transition pathway in place soon will increase the likelihood of achieving the significant potential for decarbonized gases in the three Southern Cone countries.
Keywords: 330; blue' hydrogen; Argentina; biogas; Biomethane; Brazil; Chile; decarbonization; green hydrogen; Hydrogen; Natural gas; Renewable Energy; Southern Cone